Asymptotic Characteristics of Compact Sets and Stepanets Classes - Kotlyar, B. D. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain estimates for the ε-entropy and ε-capacity of sets of periodic functions with mean value zero that have a (ψ, β)-derivative belonging to the space L 2(0, 2π).